PHYSICO-CHEMICAL PARAMETERS OF SIBERIAN LARCH (LARIX SIBIRICA) BARK EXTRACTED WITH WATER-AMINO-ALCOHOLIC EXTRACTANTS - Petrunina, Elena Alexandrovna; Shapchenkova, OlgaOlga Aleksandrovna; Loskutov, SergeySergey Redzhinaldovich (Химия растительного сырья, 2021)
This paper presents the results of a thermal analysis, that involved thermogravimetry (TG/DTG) and differential scanning calorimetry (DSC), of natural bark of Siberian larch (Larix sibirica Ldb.) vs. the bark extracted with 5% water-monoethanolamine (MEA) and (vs.) 5% water-triethanolamine (TEA). Thermogravimetric data obtained in an oxidative (air) atmosphere allowed us to identify temperature ranges of thermal decomposition stages for the larch bark samples, as well as to determine the corresponding mass loss and mass loss rate at programmed heating. The Ozawa-Flynn-Wall (OFW) method was used to calculate the dependence of activation energy of the thermal decomposition of experimental samples on the conversion degree (Еа = f(a)); the symbate run of Еа = f(a) curves was established. The DSC data obtained agreed with those of TG/DTG. The integral heat of the bark thermal decomposition (9.60 kJ/g and 14.12 kJ/g for MEA and TEA, respectively) indicated the bark to be competitive with other biofuels, such as briquetted lignin, wood pellets, sunflower husk, rapeseeds, and straw.